2014
DOI: 10.1364/oe.22.027102
|View full text |Cite
|
Sign up to set email alerts
|

Balanced optical-microwave phase detector for sub-femtosecond optical-RF synchronization

Abstract: We demonstrate that balanced optical-microwave phase detectors (BOMPD) are capable of optical-RF synchronization with sub-femtosecond residual timing jitter for large-scale timing distribution systems. RF-to-optical synchronization is achieved with a long-term stability of < 1 fs RMS and < 7 fs pk-pk drift for over 10 hours and short-term stability of < 2 fs RMS jitter integrated from 1 Hz to 200 kHz as well as optical-to-RF synchronization with 0.5 fs RMS jitter integrated from 1 Hz to 20 kHz. Moreover, we ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Several studies found that the Retinomax had high repeatability and good agreement with cycloplegic retinoscopy. 5, 13, 15, 23 In fact, the cycloplegic Retinomax has been used for comparison to measure refractive error in large epidemiological pediatric eye disease studies, including the Multi-Ethnic Pediatric Eye Disease Study and Baltimore Pediatric Eye Disease Study. 24, 25 However, Wesemann and colleagues 15 found that Retinomax measurements in children under cycloplegia provided slightly more “plus” (by a mean of 0.25–0.50 D in spherical equivalent) than subjective refraction or retinoscopy in children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that the Retinomax had high repeatability and good agreement with cycloplegic retinoscopy. 5, 13, 15, 23 In fact, the cycloplegic Retinomax has been used for comparison to measure refractive error in large epidemiological pediatric eye disease studies, including the Multi-Ethnic Pediatric Eye Disease Study and Baltimore Pediatric Eye Disease Study. 24, 25 However, Wesemann and colleagues 15 found that Retinomax measurements in children under cycloplegia provided slightly more “plus” (by a mean of 0.25–0.50 D in spherical equivalent) than subjective refraction or retinoscopy in children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…The BOMPD operation principle is based on balanced optical heterodyne detection with use of the fiber Sagnac interferometer [6]. In addition to the last modifications of the BOMPD scheme [4] with multi-GHz and, therefore, unidirectional phase modulation of the optical pulses in the Sagnac loop, we have implemented an independent RF demodulation arm for the error signal (see Figure 2). The signal demodulation is performed at the lowest possible frequency (half of the MLL repetition rate) to maximize SNR at photodetection and to minimize thermally-and humidity-induced phase drifts in the electronic and optical paths for long-term stability.…”
Section: Methodsmentioning
confidence: 99%
“…Such a perfect marriage requires a matchmaker who translates frequency and phase stability from optical domain to electronic domain, a hybrid optical-microwave phase detector (see Figure 1). Various schemes of such phase detectors were successfully implemented to the hybrid PLLs [4,5], however their high sensitivity to temperature and humidity drifts put obstacles in the way to achieve sub-1-fs RMS stability over several hours of operation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a mode locked laser (MLL) has an inherent advantage to simultaneously provide low jitter time markers and generate high performance microwave signals encoded in its repetition rate; it is therefore a promising candidate to serve as a timing reference for all antennas in this microwave network. In the past decade, we have developed a high precision timing distribution system using MLLs and balanced optical cross-correlators (BOC) [3] and demonstrated 1-fs precision local optical-to-microwave synchronization using balanced optical-microwave phase detectors (BOMPD) [4]. In this paper, we remotely synchronize two independent microwave sources over a 4.7-km fiber link network.…”
Section: Introductionmentioning
confidence: 99%